2018
DOI: 10.1097/sle.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Recurrence Rates of Nonparasitic Hepatic Cysts Treated With Laparoscopy or With Open Fenestration: A Meta-Analysis

Abstract: These findings underscore the distinct role of laparoscopy deroofing in the treatment of hepatic cysts because of the certainty of its long-term curative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The laparoscopic approach is the current standard of care, but studies documenting long-term follow-up after laparoscopic treatment of simple liver cysts have shown recurrence rates varying from 4% to 41% [16]. A meta-analysis of 31 studies performed by Zhang et al found no difference in recurrence rates between the open fenestration group and the laparoscopy group, regardless of whether it was a single or multiple hepatic cysts [17].…”
Section: Simple Cystmentioning
confidence: 99%
“…The laparoscopic approach is the current standard of care, but studies documenting long-term follow-up after laparoscopic treatment of simple liver cysts have shown recurrence rates varying from 4% to 41% [16]. A meta-analysis of 31 studies performed by Zhang et al found no difference in recurrence rates between the open fenestration group and the laparoscopy group, regardless of whether it was a single or multiple hepatic cysts [17].…”
Section: Simple Cystmentioning
confidence: 99%
“…The available studies have a retrospective single centre design. [64][65][66][67][68][69] Mere aspiration of cyst fluids invariably results in refilling of the cyst cavity with fluid. 70 Therefore, aspiration of cyst fluid without subsequent sclerotherapy should not be considered as definitive volume-reducing therapy.…”
Section: Recommendationsmentioning
confidence: 99%
“…65 Laparoscopy is preferred over laparotomy in view of the shorter procedural time, reduced postoperative hospital stays and less postoperative pain, while recurrence rates and symptom relief are comparable to the open approach. 64,67,69 More extensive surgical procedures such as partial hepatectomy combined with cyst fenestration in PLD have been associated with a perioperative mortality rate of up to 14% and postoperative liver failure (mean follow-up time up of 6 and 8 years) with the need for liver transplantation in 2-3% of patients. 46,72 Different volume-reducing therapies have not been directly compared in the literature and as a consequence robust evidence on the superiority of any of available volume-reducing therapies is absent.…”
Section: Recommendationsmentioning
confidence: 99%
“…Unroofing liver cysts can be undertaken as an open or laparoscopic surgery[ 25 ]. Laparoscopic unroofing has become the gold standard treatment with low recurrence rates between 0% and 13.8%[ 26 , 27 ]. Some centres employ fulguration of the cyst bed and omental transposition to reduce the risk of cyst recurrence[ 28 ].…”
Section: Discussionmentioning
confidence: 99%